Effective Constrained Handling by Hybridized Cuckoo Search Algorithm with Box Complex Method. Issue 2 (December 2017) - Zade, Anita; Patel, Narendra; Padhiyar, Nitin
Abstract: Cuckoo search algorithm (CSA) is an evolutionary optimization algorithm, which requires an additional constraint handling mechanism. While CSA has been successfully applied for exploring the search space, it lacks good convergence property near the optimum point. On the other hand Box Complex method (BCM) has good local convergence property. This paper presents a hybrid cuckoo search algorithm (CSA) with effective constraint handling mechanism by Box Complex method (BCM). Each infeasible member is processed using BCM by projecting it through the centroid of a fixed number of feasible members. This hybridization approach provides good convergence rate along with an effective constraint handling technique. To demonstrate the efficacy of the proposed algorithm, a comparative study with the other popular algorithms has been presented using eleven test problems and an optimal grade transition problem.